Pengaruh Suhu dan Waktu Pemanggangan terhadap Mutu Fisik Organoleptik Roll Cake - Raditya Akbar Prayata; Gearyl Mearchyello; Razita Nazla Afiqah; Arsylla Zahrani Putri; Revika Putri Rahmadhani; Mazaya . (GLOBAL SCIENTS PUBLISHER, 2026)
The baking process is a crucial stage in roll cake production as it significantly determines the physical quality and flexibility of the cake during rolling. This laboratory experimental study aimed to analyze the effects of baking temperature and duration variations on the density and organoleptic quality of roll cakes, while determining the most optimal treatment combination. The method employed was an experiment utilizing the all-in-one batter method, divided into three treatments: Treatment 1 (160°C, 25 minutes), Treatment 2 (170°C ,20 minutes), and Treatment 3 (180°C, 15 minutes). The evaluation parameters included physical characteristics (height increase, weight loss, and geometric density) and sensory testing by trained panelists. The results indicated that variations in these parameters significantly affected both the physical and sensory properties, particularly texture and appearance. The low-temperature treatment (Treatment 1) produced the best product, exhibiting the highest volume expansion, lowest density, and a flexible crumb that rolled without cracking. Conversely, the high-temperature treatment resulted in a dense cake with a high risk of cracking. In conclusion, a balance of low temperature and a longer baking duration is highly recommended to produce roll cakes with optimal physical and sensory qualities.